The economic importance of oil transport in the OPEC countries with special reference to the Iraqi oil tanker company - الجزائري , حسين حيدر محمد (Journal of Petroleum Research and Studies, 2020)
Crude oil, refined products and gas considered as the most important products in terms of value and quantity in maritime shipping, as many types of crude oil, petroleum and chemical products are transported by specially designed vessels. The tanker markets witnessed several developments in this field, the oil producing and exporting countries should keep pace of maintain and stabilize the world markets for oil transportation. Some OPEC countries such as Kuwait and Saudi Arabia have been able to keep abreast of the developments in oil shipping، they diversified their vessels and increase their number because it considered as one of the largest producer countries and exporting oil products in international markets specially Saudi Arabia which consider the largest producer in OPEC organization and has a fleet of 46 VLCC (Very Large Crude Carrier). Therefore, Iraq is still taking slow steps in pursuing these developments، Iraqi Oil Tankers Company still have (4) small vessels with (53) thousand tons tonnage، although Iraq is the second largest oil producer within the OPEC countries and it should be own a fleet and a strong competitor in the international oil shipping markets.